Socio Demographic and Economic Factors Associated with Intrauterine Growth Retardation in Far Western Nepal - Bhatt, Madan Raj (Nepal Population Journal, 2026)
Birth weight is determined by the duration of gestation and the intrauterine growth rate. Intrauterine growth retardation (IUGR) is an important public health problem causing low birth weight. This paper aims to describe the relationship between sociodemographic and economic factors and IUGR in far western Nepal. An institution-based nested case-control study was conducted in Seti and Mahakali provincial (then regional) hospitals. The cohort of pregnant mothers was followed for the possible result of producing either cases or controls. Altogether, 98 cases and 196 controls were identified after following the cohort of full-term pregnant mothers. Face-to-face interviews were done with mothers to collect the data using a structured questionnaire. One-to-one matching was done for the age and ethnicity of the mother and the sex of the newborn. The odds ratio was used to estimate the magnitude of the association between suspected risk factors and IUGR. The average weight gain during pregnancy was 5.6 kg among cases and 6.54 kg among the control group. The mean birth weight of newborns among cases was nearly 2218 grams, and that of the control was 2962 grams. In the bivariate analysis, age at marriage, illiteracy, housing condition, history of low birth weight (LBW), less than 4 antenatal care (ANC) visits, low iron consumption during pregnancy, lack of regular consumption of milk and milk products, vegetables and fruits, low food consumption, not getting financial support from family members, and feeling stress during pregnancy were found to be associated with IUGR. In multivariate conditional logistic analysis, a history of LBW, fewer than four ANC visits, and a lack of regular consumption of fruits during pregnancy were identified as independent risk factors for IUGR. Focused interventions for service utilization and care during pregnancy, both from health institutions and from the family, are the keys to controlling IUGR